PENGEMBANGAN INSTRUMEN ASESMEN STRES BERBASIS JARINGAN BAGI SISWA SMA/SMK YANG MENJALIN HUBUNGAN ROMANTIS - Afridayani; Metri Elvianika; Yustinus Windrawanto; Adhi Krisna Maria Agustin (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Romantic relationships in adolescents have the potential to produce several impacts, namely the emotional, cognitive, behavioral, physical, and academic conditions of students. In Indonesia, no web-based instrument specifically designed to measure adolescent stress contextually within romantic relationships is yet available. A web-based instrument was developed because it allows access anytime and anywhere, automatic data processing, and real-time presentation of results to users. This study develops a web-based stress assessment instrument for senior high school (SMA/SMK) students who are in romantic relationships, using an R&D approach based on the Borg and Gall model modified into seven stages. The instrument was adapted from the Kessler Psychological Distress Scale (K10) with the addition of three contextual indicators covering physical, academic, and behavioral aspects, resulting in 13 statement items on a 5-point Likert scale accessible at stressmater.my.id. The product's advantages include a responsive interface that is user-friendly for adolescents, automatic assessment results accompanied by interpretations and recommendations, and a feature for integrating the name of the school counselor (BK) corresponding to the respondent's school. Validation results indicate a design feasibility of 77% (Good) and content feasibility of 90% (Very Good), with user satisfaction at 89.8% (Very Good). Field testing involving 31 students revealed that 83.87% fell into the high stress category.